2014
DOI: 10.1007/s00442-014-3110-8
|View full text |Cite
|
Sign up to set email alerts
|

Personality affects the foraging response of a mammalian herbivore to the dual costs of food and fear

Abstract: Predators attack and plants defend, so herbivores face the dilemma of how to eat enough without being eaten. But do differences in the personality of herbivores affect the foraging choices of individuals? We explored the ecological impact of personality in a generalist herbivore, the brushtail possum (Trichosurus vulpecula). After quantifying personality traits in wild individuals brought temporarily into captivity, we tested how these traits altered foraging by individuals when free-ranging in their natural h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 88 publications
3
38
0
Order By: Relevance
“…We incorporated an aspect of individual behaviour in the form of a personality trait into our model to allow females to respond to disturbance in different ways. We chose this as an example because personality traits influence foraging behaviour (Patrick & Weimerskirch 2014;Mella et al 2015), thus may influence the behavioural reactions of an individual to disturbance (Martin & R eale 2008). When a female arrived at the optimal patch and discovered it was disturbed she could: (i) continue foraging in the disturbed patch at a reduced probability of finding prey (q); or (ii) move to the optimal alternative patch at an increased energy cost (c e ) and mortality risk (c s ).…”
Section: The Income Breedermentioning
confidence: 99%
“…We incorporated an aspect of individual behaviour in the form of a personality trait into our model to allow females to respond to disturbance in different ways. We chose this as an example because personality traits influence foraging behaviour (Patrick & Weimerskirch 2014;Mella et al 2015), thus may influence the behavioural reactions of an individual to disturbance (Martin & R eale 2008). When a female arrived at the optimal patch and discovered it was disturbed she could: (i) continue foraging in the disturbed patch at a reduced probability of finding prey (q); or (ii) move to the optimal alternative patch at an increased energy cost (c e ) and mortality risk (c s ).…”
Section: The Income Breedermentioning
confidence: 99%
“…1). Individuals may differ physiologically (e.g., detoxification capacity, stress hormones, metabolism; Maltby 1999, Montooth et al 2006 or behaviorally (e.g., boldness; Mella et al 2014). For example, individual brushtail possums (Trichosurus vulpecula) varied in measures of boldness, and boldness influenced foraging at patches with high predation risk and patches with low predation risk only when food toxins were low (Mella et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals may differ physiologically (e.g., detoxification capacity, stress hormones, metabolism; Maltby 1999, Montooth et al 2006 or behaviorally (e.g., boldness; Mella et al 2014). For example, individual brushtail possums (Trichosurus vulpecula) varied in measures of boldness, and boldness influenced foraging at patches with high predation risk and patches with low predation risk only when food toxins were low (Mella et al 2014). However, Simpson and Raubenheimer (1999) found that locusts that were dietary specialists (Locusta gregaria) were more likely to minimize the error of overeating one nutrient and undereating another than were generalist locusts (Schistocerca gregaria), presumably because the generalists would be more likely to later encounter and consume a plant with a complementary imbalance to the present food, allowing the ingested excess from the current food to balance the deficit in the subsequent one.…”
Section: Discussionmentioning
confidence: 99%
“…Foraging is a three-stage process in which animals have to first find food, then handle and consume it and finally determine when to quit. However, much of the foraging ecology theory is about why animals quit food patches (Charnov, 1976;Krebs, 1977;Pyke, 1984), with empirical tests of habitat (Kotler, Brown, & Hasson, 1991) and forager characteristics (Mella, Ward, Banks, & Mcarthur, 2015) that foragers use to decide when to leave. Many studies focused on understanding what characteristics of a food patch make it costly for foragers to stay and have often used the giving-up-density approach (GUD; Brown, 1988) to reveal the mechanisms behind quitting a patch (for a review, see Bedoya-Perez, Carthey, Mella, McArthur, & Banks, 2013), without exploring the reasons that attract animals to that patch.…”
Section: Introductionmentioning
confidence: 99%